HUKUM ADAT TERHADAP PENCEMARAN DAN PENGERUSAKAN LINGKUNGAN DI DESA SUNGAI ULUK PADA MASYARAKAT SUB SUKU KANTUK KOTA PUTUSSIBAU KABUPATEN KAPUAS HULU KALIMANTAN BARAT - Genopepa Sedia (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2021)
The Cycles of life Daya’ Kantuk is known as agrarian with rice farming ( Oryza Sativa L ) for shifting cultivation system with a cycle of 7 (seven)-10 (ten) years to be replanted. It is not surprise that along the river, peoples have a lot of land or agricultural land scattered along the roads and rivers. Meanswhile the forest areas arebelong to wildlife reserves, hunting, and forest building materials. The Dayak Kantuk have a strong relationship with various other Dayak sub- tribes: Iban , Ketungau , Seberuang , Desa and Mualang . The differences are the dialect of the language and some certain vocabulary. People adhered that the origin of the existence of Dayak Kantuk tribe is started from Tampun Juah area. It is located in the lower reaches of the Sekayam River near the Segumon area. Dayak Kantuk is one of the Dayak sub-tribes of the Ibanic family which is widespread in Kapuas Hulu Regency (West Kalimantan). It is call as kinship because the Kantuk tribe share the same language as the Iban tribe as well as the Seberuang Dayak, Mualang, Bugau, Sebaru’ and others. The Kantuk Dayak tribe lives in the Long House or called as Rumah Betang.In regarding this customary law will be reviewed in five years, the existing provisions will be effective for all levels of the Kantuk tribe without exception. This provision came into force on May 12, 2006. Therefor, for all provisions of customary law of the Dayak Kantu tribe done previously is declared no longer valid. All customary instruments are expected to disseminate and guide all the underlined provisions in resolving any problems and the various shortcomings found in their implementation that should be taken into account for future improvements are noted.